Cost Analysis of an Unreliable Retrial Queue Subject to Balking, Bernoulli Vacation, Two Types of Service and Starting Failure - Arivudainambi, D.; Gowsalya, M. (Computational Intelligence, Cyber Security and Computational Models. Models and Techniques for Intelligent Systems and Automation, 2018)
The proposed queueing model deals with a single server retrial queueing subject to balking, Bernoulli vacation, two types of service and starting failure. Single server provides two types of heterogeneous service in which the customer will choose either type 1 service or type 2 service with two different probabilities. The authors assume that, while rendering service to the arriving primary or repeated customers the server may subject to starting failure. After each service completion the server will take vacation subject to Bernoulli vacation policy. For such queueing model the necessary and sufficient condition have been derived. The model have been solved by the use of supplementary variable technique. Cost analysis have been carried out with the cost parameters. To validate the proposed model some performance measures, special cases and sensitivity analysis have been discussed.